Autoimmunity in Common Variable Immunodeficiency - Agarwal, Shradha (2009)
Common variable immunodeficiency (CVID) is the most common clinically significant primary immune defect. Although the hallmark of CVID is hypogammaglobulinemia, the intrinsic dysregulation of the immune system leads to defective T-cell activation and proliferation, as well as dendritic cell and cytokine defects. Although 70% to 80% of patients have had recurrent sinopulmonary infections, auto-immunity and inflammatory complications are also common. The most common autoimmune conditions are immune thrombocytopenic purpura and hemolytic anemia, but other autoimmune complications arise, including rheumatoid arthritis, pernicious anemia, primary biliary cirrhosis, thyroiditis, sicca syndrome, systemic lupus, and inflammatory bowel disease. Treatment of autoimmunity includes high-dose immunoglobulins, corticosteroids, selected immunosuppressants, and other immune modulators. This review focuses on autoimmune conditions associated with CVID, potential mechanisms of immune dysregulation, and therapeutic strategies.